Translation Learning through the Stylistic of Holy Qur'an - Harishul Ilmi; Mu'asshomah; Halimi Zuhdy (UIN Syekh Wasil Kediri, Indonesia, 2025)
Abstract: This study aims to develop a translation teaching model based on Qur'anic linguistic styles to bridge the theoretical and practical gap in translation pedagogy. This research employed a qualitative descriptive-analytical approach through library research to analyze the style of QS. Al-'Alaq (1-5) as a pedagogical model. The findings reveal three main stylistic patterns: uslūb al-amr al-ta'līmī (educational imperative style in iqra' bi ismi rabbik) representing gentle pedagogical communication; uslūb al-takrār al-tarbawī (educational repetition) that reinforces meaning through reflection; and uslūb isti'ārah ta'līmiyyah (educational metaphor in 'allama bi al-qalam) emphasizing language symbolism as a means of knowledge transmission.Based on these findings, a